2011
DOI: 10.1021/la104590k
|View full text |Cite
|
Sign up to set email alerts
|

Ionization Behavior of Amino Lipids for siRNA Delivery: Determination of Ionization Constants, SAR, and the Impact of Lipid pKa on Cationic Lipid−Biomembrane Interactions

Abstract: Ionizable amino lipids are being pursued as an important class of materials for delivering small interfering RNA (siRNA) therapeutics, and research is being conducted to elucidate the structure-activity relationships (SAR) of these lipids. The pK(a) of cationic lipid headgroups is one of the critical physiochemical properties of interest due to the strong impact of lipid ionization on the assembly and performance of these lipids. This research focused on developing approaches that permit the rapid determinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
79
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 41 publications
(96 reference statements)
2
79
0
Order By: Relevance
“…Studies have shown that the ability of materials to take on a positive charge with decreasing pH may confer transfection efficacy which would point to pKa as a critical parameter 35,40 . Data in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the ability of materials to take on a positive charge with decreasing pH may confer transfection efficacy which would point to pKa as a critical parameter 35,40 . Data in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of these three, the LNP pK a showed the strongest correlation with biological barriers and gene silencing. LNP pK a was measured using a well-known 2-(p-toluidino)-6-napthalene sulfonic acid (TNS) assay (17,39) by titrating the LNPs from pH 2.5-8.5. The pK a of each fully formulated LNP was determined from the resulting fluorescence titration S-curve using a curve-fit analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The pK a of each fully formulated LNP was determined from the resulting fluorescence titration S-curve using a curve-fit analysis. The advantage of this method is that LNP structure and formulation are taken into account and thus the measured pK a represents that of the LNP as a whole rather than just the individual lipid (17). The measured pK a values (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a LNP formulation based on DLin-MC3-DMA (16), one of the most potent lipids identified in this work, is currently being utilized in a clinical trial for treating hypercholesterolemia; the target is PCSK9 and the data (not shown) indicate decreases in LDL-C after a single low dose. [17,18] Received: April 27, 2012 Published online: July 10,2012 . Keywords: drug delivery · gene silencing · ionizable amino lipids · liposomes · siRNA …”
mentioning
confidence: 99%